2006
DOI: 10.1007/s00261-006-9049-4
|View full text |Cite
|
Sign up to set email alerts
|

Biliary atresia in infants with prolonged cholestatic jaundice: diagnostic accuracy of hepatobiliary scintigraphy

Abstract: Hepatobiliary scintigraphy is an important imaging technique in the diagnostic evaluation of infants with prolonged cholestatic jaundice. It is a convenient and reliable method of differentiating BA from NHS, with a diagnostic accuracy superior to that of US but slightly inferior to that of liver biopsy. Ultrasonography is the least sensitive and specific available modality and its findings should be confirmed by scintigraphy or liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…With the intention of finding a non-invasive test that differentiates exactly between hepatocellular and obstructive jaundice, several diagnostic tools have been investigated. Representative studies that refer to sensitivity and specificity of particular examinations are listed in Table 1 [14][15][16][17][18][19][20][21][22][23]. However, all studies contained only small numbers of BA patients (4-48 patients), and the sensitivity and specificity varied widely.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With the intention of finding a non-invasive test that differentiates exactly between hepatocellular and obstructive jaundice, several diagnostic tools have been investigated. Representative studies that refer to sensitivity and specificity of particular examinations are listed in Table 1 [14][15][16][17][18][19][20][21][22][23]. However, all studies contained only small numbers of BA patients (4-48 patients), and the sensitivity and specificity varied widely.…”
Section: Discussionmentioning
confidence: 98%
“…Sensitivity and specificity were calculated for predicting BA in neonatal jaundice by using receiver operating characteristic curves. The statistical analysis was performed with the Statistical Package and Software Solution v. 15.0 (SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Slow uptake of the injected radioisotope or nonvisualization of the liver with persistence of the cardiac pool suggests hepatocellular dysfunction, whereas nonvisualization of the radioisotope in the small intestine at 4 to 24 hours suggests either bile duct obstruction or the severe inability of the hepatocyte to secrete. The sensitivity of scintigraphy for BA is relatively high (83%–100%); however, its specificity is low (33%–80%), (15)(16) limiting its use to differentiate BA from other nonsurgical conditions. Pretreatment with phenobarbital may increase test sensitivity.…”
Section: Evaluation Of Neonatal Cholestasismentioning
confidence: 99%
“…It clears fast from blood, excretes less through kidney and is less affected by the serum bilirubin concentration. Nadel [4], Charearnrad [5], and Esmaili [6] reported that the accuracy of 99m Tc-EHIDA hepatobiliary imaging can be higher than 95%. The current study showed that the sensitivity, specificity, and accuracy of 99m Tc-EHIDA hepatobiliary imaging in diagnosing biliary atresia were 100%, 74.5%, and 83.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%